Women’s participation in decision-making for the type of anaesthesia for childbirth: a qualitative study in Pakistan - Bibi, Margus; Raisa Begum Gul; Kainat Asmat; Muhammad Nasir Ayub Khan (Journal of the Pakistan Medical Association, 2026)
Objective: To explore women’s participation in decision-making related to the type of anaesthesia for elective caesarean section. Method: The exploratory, descriptive qualitative study was conducted from June to August 2021, and comprised women aged at least 18 years who were either planned for elective caesarean section or had undergone elective caesarean section at a tertiary care hospital in Islamabad, Pakistan, and a secondary care hospital in the mountainous northern areas of the country. was triangulated via semi-structured interviews and observations. Data was subjected to manual content analysis, and codes were assigned based on manifest and latent information. The codes were merged to form categories, and a theme was extracted after repeated reflection on the categories. Results: Of the 20 women with age ranging 25-38 years, 11(55%) were from the secondary care hospital, and 9(45%) were from the tertiary care hospital. Overall, 11(55%) women received general anaesthesia and 9(45%) received spinal anaesthesia. Data saturation was achieved in the 14th interview (70%), and the remaining 6(30%) subjects were observed by the researchers. Content analysis led to four categories: initiation of discussion about anaesthesia, quality of discussion about anaesthesia, opportunity for patients’ input in the decision, and factors influencing the decision. The categories led to the generation of an overarching theme: ensure the norms; follow the commands. Conclusion: The decision regarding the choice of anaesthesia for caesarean sections was usually in line with the hospitals’ unwritten standards, which were either aligned with evidence-based medical practice, or the availability and competence of anaesthesiologists. Women were usually the recipients of information by the anaesthesiologists. Key Words: Type of anaesthesia, Spinal anaesthesia, General anaesthesia, C-section, Healthcare setting, Qualitative study, Decision making.